Absence of Endothelial ERα Results in Arterial Remodeling and Decreased Stiffness in Western Diet–Fed Male Mice - Manrique-Acevedo, Camila (Endocrinology, 2017)
The role of estrogen receptor-α (ERα) signaling in the vasculature of females has been described under different experimental conditions and our group recently reported that lack of endothelial cell (EC) ERα in female mice fed a Western diet (WD) results in amelioration of vascular stiffness. Conversely, the role of ERα in the male vasculature in this setting has not been explored. In conditions of overnutrition and insulin resistance, augmented arterial stiffness, endothelial dysfunction, and arterial remodeling contribute to the development of cardiovascular disease. Here, we used a rodent model of decreased ERα expression in ECs [endothelial cell estrogen receptor-α knockout (EC-ERαKO)] to test the hypothesis that, similar to our findings in females, loss of ERα signaling in the endothelium of insulin-resistant males would result in decreased arterial stiffness. EC-ERαKO male mice and same-sex littermates were fed a WD (high in fructose and fat) for 20 weeks and then assessed for vascular function and stiffness. EC-ERαKO mice were heavier than littermates but exhibited decreased vascular stiffness without differences in endothelial-dependent vasodilatory responses. Mesenteric arteries from EC-ERαKO mice had significantly increased diameters, wall cross-sectional areas, and mean wall thicknesses, indicative of outward hypertrophic remodeling. This remodeling paralleled an increased vessel wall content of collagen and elastin, inhibition of matrix metalloproteinase activation and a decrease of the incremental modulus of elasticity. In addition, internal elastic lamina fenestrae were more abundant in the EC-ERαKO mice. In conclusion, loss of endothelial ERα reduces vascular stiffness in male mice fed a WD with an associated outward hypertrophic remodeling of resistance arteries.